Lignosulfonate Treating Bauxite Residue Dust Pollution: Enhancement of Mechanical Properties and Wind Erosion Behavior - Ding, X.; Xu, Guang; Kizil, M.; Zhou, W.; Guo, X. (Springer, 2018)
Red sand is the by-product of aluminum refinery processing. It is susceptible to wind erosion and the emitted particles may cause serious environmental and safety issues. Lignosulfonate stabilizers are one of the promising non-traditional stabilizers to mitigate such issues. However, the contribution of the improvement on each mechanical property to the modification of the final erosion resistance was rarely analyzed, especially for coarse sandy bauxite residue. Thus, this study was conducted to analyze the relationship between improved mechanical properties and corresponding dust control performance of bauxite residue by applying two lignosulfonate stabilizers LS-S and LS-C. Results show that both of them provide improved water retention with higher concentration. However, the improvement is not substantial when the concentration is more than 4%. Two stabilizers generate nearly the same results in the optimum moisture content (OMC) and maximum dry density (MDD) tests, in which both of them reduce the OMC by about 10% and slightly increase the MDD. The addition of LS has virtually no influence on the density of the formed crust, but the crust thickness reduces with the increase of LS concentration. Furthermore, both penetration resistance and unconfined compressive strength (UCS) evidently increase with LS concentration, and LS-S apparently outperforms LS-C. Wind erosion tests have demonstrated that both LS-S and LS-C improve wind erosion resistance, and LS-S-treated sample can withstand longer period of wind attack, which is consistent with the penetration and UCS results that LS-S outperforms LS-C. Importantly, evidences presented in this paper illustrate that the improved mechanical properties appear to increase dust control performance.